CHASER: an innovative satellite mission concept to measure the effects of aerosols on clouds and climate - Rennó, Nilton O.; Williams, Earle; Rosenfeld, Daniel; Fischer, David G.; Fischer, Jürgen; Kremic, Tibor; Agrawal, Arun; Andreae, Meinrat O.; Bierbaum, Rosina; Blakeslee, Richard; Boerner, Anko; Bowles, Neil; et al. (Bulletin of the American Meteorological Society, 2013)
The formation of cloud droplets on aerosol particles, technically known as the activation of cloud condensation nuclei (CCN), is the fundamental process driving the interactions of aerosols with clouds and precipitation. The Intergovernmental Panel on Climate Change (IPCC) and the Decadal Survey indicate that the uncertainty in how clouds adjust to aerosol perturbations dominates the uncertainty in the overall quantification of the radiative forcing attributable to human activities. Measurements by current satellites allow the determination of crude profiles of cloud particle size, but not of the activated CCN that seed them. The Clouds, Hazards, and Aerosols Survey for Earth Researchers (CHASER) mission concept responds to the IPCC and Decadal Survey concerns, utilizing a new technique and high-heritage instruments to measure all the quantities necessary to produce the first global survey maps of activated CCN and the properties of the clouds associated with them. CHASER also determines the activated CCN concentration and cloud thermodynamic forcing simultaneously, allowing the effects of each to be distinguished.
Gesehen am 03.01.2022